Strategic knowledge management technology - Gottschalk, Petter 1950- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
This title applies the knowledge-based view of the firm, which builds on the resource-based theory. The value shop is identified as the typical value configuration for knowledge firms. This book applies a stages of growth model for knowledge management technology, where firms develop from the person-to-tools strategy, via the person-to-person strategy and the person-to-documents strategy, to the person-to-systems strategy. The case of law firms is extensively explored. IS/IT strategy for knowledge management is developed within the framework of the Y model